Antibiotics prescription pattern and compliance for common childhood illnesses – an observational study - Dr. Shanthi AK; Dr. C. Barathy; Dr. Antonieo Jude Raja; Dr. Vijayadevagaran (Pediatric Review: International Journal of Pediatric Research, 2017)
Introduction: Antibiotics are generally overused in children. Frequent inappropriate use of antibiotics and poor compliance contributes to antibiotic resistance. An observational study was undertaken to determine the pattern of antibiotic use and compliance for common ailments in children attending a tertiary care hospital in Puducherry, South India.Methods: Data was obtained from 197 consecutive children who had visited a health care provider during the previous two weeks for any ailment, in a pretested semi structured questionnaire. Data was entered on MS Excel spreadsheet and analysed using Stata14.0 (Stata Corp, College Station, Tx). Chi square test with Fisher’s modification and logistic regression models were used in the analysis.Results: Acute respiratory infections were the most common infections in all age groups followed by diarrheal disorders in infants and fever in older children. Proportion of illnesses which received antibiotics was 75% for respiratory illnesses, 78% for fever, 50% for diarrheal disorders and 64% for other infections, there being no statistically significant difference between them. Out of 143 children who were prescribed antibiotics, 127 (89%) gave the medicines as prescribed. However, only 53 (37%) completed the full course of antibiotics. Compliance with treatment was not associated with age or the type of illness. Most of the parents (73%) discontinued antibiotics because of worsening of symptoms. Adverse reaction to antibiotics was seen in 32 (22%) children.Conclusion: Overuse of antibiotics for common ailments and poor compliance with treatment were perhaps important contributory causes for development of antimicrobial resistance in this region.